2014
DOI: 10.12740/app/31780
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary habits of patients with recurrent depressive disorders

Abstract: Aim. The aim of this study was evaluation of selected dietary habits of patients with recurrent depressive disorders. methods. The study included 150 patients (75 patients suffering from recurrent depressive disorders. and 75 healthy people aged 18-64 years). The assessment of dietary habits was carried out by using a food frequency questionnaire. Results. It has been shown that in the compared groups of women, patients with depression consumed significantly less groats (p<0.001), rice (p= 0.02), red meat (p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…For females, the significant predictor of depression was food insecurity, and for anxiety, the significant predictors were added sugars intake and food insecurity. These findings are consistent with previous studies showing differences in dietary patterns of males and females with mental health disorders [ 26 , 27 , 28 ]. These are also consistent with studies showing links between mental health and both dietary intake [ 26 , 27 , 28 , 29 , 30 ] and food insecurity [ 5 , 6 , 7 , 8 , 9 , 10 ], with lower intakes of healthy foods and higher rates of food insecurity showing an increase in prevalence of mental health symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For females, the significant predictor of depression was food insecurity, and for anxiety, the significant predictors were added sugars intake and food insecurity. These findings are consistent with previous studies showing differences in dietary patterns of males and females with mental health disorders [ 26 , 27 , 28 ]. These are also consistent with studies showing links between mental health and both dietary intake [ 26 , 27 , 28 , 29 , 30 ] and food insecurity [ 5 , 6 , 7 , 8 , 9 , 10 ], with lower intakes of healthy foods and higher rates of food insecurity showing an increase in prevalence of mental health symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…There is a strong relationship between nutrition and mental health in adults [ 26 , 27 , 28 , 29 , 30 ] and has been found to differ between depressed and anxious individuals [ 26 , 27 , 28 ]. Further, diet intake has been found to differ between males and females with mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding health and lifestyle, without any changes in sleep duration, meal size, appetite, the residence(urban/rural) and anxiety or depression all were associated with a good diet quality. The link between mental health and dietary intake is consistent in various studies (Meegan et al, 2017;Ohmori et al, 2017;Stefańska et al, 2014), with lower healthy food intake and higher food insecurity rates indicating an increase in anxiety and depression. Those with greater stress and anxiety levels tend to not follow careful food selection, eat larger quantities and more than they need to, thus regulating emotions via food (Braden et al, 2018;Schneider et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Part of the studies were about milk and depressive symptoms or disorders. In a Polish cross-sectional study of 150 men and women, no association of milk and clinically diagnosed depression was observed (11) . While a cohort study found that lower milk intake was related to increased risk of depressive symptoms in men, whereas these relationship were not statistically significant in women (4) .…”
mentioning
confidence: 96%